Evaluation of risk adjusted performance of mutual funds in an emerging market. (6th February 2021) - Ali, Muhammad Asad; Aqil, Muhammad; Alam Kazmi, Syed Hasnain; Zaman, Syed Imran
Abstract: The objective of this study is to find the efficiency of an emerging‐market (Pakistan) mutual funds, with reference to different measures of risks that contradict each other. We have measured risk‐adjusted performance of open‐ended equity funds of mutual funds. The reason for selecting equity funds is that it is consistent with the proxy benchmark as 100‐index. As 100‐index is also tracked by equities and equity funds that also consist of equity investment, it will be more appropriate to select equity funds. So, this study is limited to equity funds traded in Pakistan. The novelty of this study is its introduction of the Martin or Ulcer ratio, which is rarely used in Pakistani literature. This study will also limit the period under consideration from 2011 to 2019 to exclude the years 2008 to 2011 due to the crisis faced by the financial market in 2008 after which it took about two to three years to get the market back to its normal course. The statistics and probability values did not provide sufficient evidence to reject the hypothesis of market efficiency. The values support the efficient market hypothesis that even experienced and qualified funds manager, having sound market insights, cannot earn returns above the market, that is, the average returns of market and the average returns of each fund are equal. On the other hand, the risk adjusted returns including Sharpe, Treynor, Jensen's and Ulcer measures, are all on average negative. There may be qualitative factors affecting the returns to be equal or less than the risk free and market returns. Further research can explore the qualitative factors, for example, managers' qualification, funds goodwill, political instability and macroeconomic factors affecting the returns of funds.